Factors affecting the purchase decision of skincare products: Perspectives of promotion, product quality, and price - Wahyuningrum, Maria Y Aryati (Institute of Computer Science (IOCS), 2025)
This research seeks to ascertain the impact of promotion, product quality, and price on the purchase decision of Skintific skincare products. The analysis method used in this research employs qualitative primary data. The tests conducted are: validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, t-test, F-test, and coefficient of determination test. The data used in this study was collected through questionnaires, with 100 valid respondents. Non-probability sampling combined with incidental sampling is the sampling strategy employed in this study. SPSS is the testing instrument utilized. The results show that the promotion variable does not have a direct or partial effect on consumer purchase decisions, while the product quality and price variables have a direct or partial effect on the purchase decision of Skintific skincare products. The most dominant variable affecting the purchase decision is the price variable.